Wood-wind instruments at the cross-roads : a survey of recent changes - Honey, Albert Edward (Rhodes University, Faculty of Humanities, Department of Music, 1969)
Since the rise of the "Stile Rappresentative" early in the seventeenth century, the composer has made definite and increasing demands on specific performance and tonal combination of instrumentalists which has materially affected the developnent in technique and, consequently, the improvement in construction and design of every musical instrument. The monodic "Stile Rappresentative" required expressive instruments with an extensive range to match the singers and, consequently, many instruments of the Renaissance period were rendered obsolescent. For instance, the shawms, pommers and crumhorns disappeared from concerted music-making with the exception of military and outdoor use, mainly in German windbands. More flexible instruments were required, and thus cornetts, flutes (mainly recorders and fipple-flutes), oboes and bassoons came gradually into their places, which for the main part they have occupied in the orchestra ever since that time. The String sections, too, underwent radical changes. A gradual metamorphosis from the Consort of Viols to the Violin Family took place following the work of the craftsmen Gasparo da Salá»‘ (1540 - 1609) and Giovanni Paolo Maggini of Brescia, perfected by the famous Cremonese school founded by Andrea Amati and continued by Stradivarius.
Keywords: Woodwind instruments; Woodwind instruments -- History